Türkiye’de İlkokul/İlköğretim Programlarının Felsefi Temeller Açısından İncelenmesi (1924-2018) - Akdağ, Hakan; Çi̇ydem, Erol (Vakanuvis International Journal of Historical Researches, 2021)
The primary/primary education programs implemented in Turkey from the proclamation of the Republic to the present (2021), in chronological order, are as follows: 1924, 1926 Primary School Program, 1936 Primary School Program, 1948 Primary School Program, 1968 Primary School Program, 1998 Primary Education Program, 2005 Primary Education Program and 2018 Primary School program. Apart from these, there are also Primary School Program Drafts prepared in 1962 and 2015. Some of these were put into effect in the following years. The mentioned programs have been studied in the literature in various dimensions, but no study has dealt with the said programs from a holistic perspective and explains the philosophical foundations underlying them. Based on this shortcoming, in the study, the philosophies affected in the preparation of primary school programs in Turkey were determined, and evaluations were made on the reasons for the preference of these philosophies. In this direction, the study aims to evaluate the primary school/primary education programs that have been implemented in Turkey since the proclamation of the Republic by analyzing them in terms of philosophical foundations. The historical research method was used in the study, and the data were collected by the document analysis method. The descriptive analysis method was preferred in the analysis of the data. Realism, pragmatism and naturalism on the programs in question; In the first two programs, which were prepared in the 2000s, it was seen that there were the effects of the constructivist approach in addition to the mentioned philosophical movements.

Türkiye’de Cumhuriyet’in ilanından günümüze (2021) kadar uygulanmış ilkokul/ilköğretim programları kronolojik sıra ile şöyledir: 1924, 1926 İlkokul Programı, 1936 İlkokul Programı, 1948 İlkokul Programı, 1968 İlkokul Programı, 1998 İlköğretim Programı, 2005 İlköğretim Programı ve 2018 İlkokul Programı. Bunlar dışında 1962 ve 2015 yıllarında hazırlanmış İlkokul Program Taslakları mevcuttur. Söz konusu programlar çeşitli boyutlarda literatürde çalışma konusu edinilmiştir. Fakat söz konusu programları bütüncül açıdan ele alarak, bunların arka planında yatan felsefi temelleri açıklamayı konu edinen çalışma yapılmamıştır. Bu eksiklikten yola çıkılarak bu çalışmada Türkiye’de ilkokul programlarının hazırlanmasında etkilenen felsefeleri belirleyerek, söz konusu felsefelerin tercih edilme sebepleri üzerine değerlendirmelere yer verilmiştir. Yani çalışmanın amacı, Türkiye’de Cumhuriyet’in ilanından günümüze kadar uygulanmış olan ilkokul/ilköğretim programlarını felsefi temeller açısından analiz ederek değerlendirmek amaçlanmıştır. Çalışmada tarihsel araştırma yöntemi kullanılmış ve veriler doküman incelemesi yöntemi ile toplanmıştır. Verilerin analizinde içerik analizi yöntemi tercih edilmiştir.
Keywords: Primary School Curriculum; Philosophy of Education; History of Education; İlkokul Programı; Felsefi Temel; Eğitim Tarihi; İnceleme; 4. Education